1983
DOI: 10.1007/bf02175945
|View full text |Cite
|
Sign up to set email alerts
|

Secondary corneal amyloidosis: clinical and pathohistological examinations

Abstract: A patient suffering from an excentric vascularized tumorlike corneal change is reported who submitted to a penetrating optic keratoplasty. The diagnosis of a secondary corneal amyloidosis was established by histological examination. The clinical course and pathological findings by means of light- and electron microscopy are described and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…This condition has been asso ciated with retrolental fibroplasia, phlyc tenular keratoconjunctivitis, lipoid degen eration. penetrating wound, keratokonus, buphthalmos, and trichiasis [1][2][3][4][5][6]. To our knowledge, only a few reported cases have been described of secondary corneal amyloi dosis caused by trichiasis [4.…”
Section: Introductionmentioning
confidence: 99%
“…This condition has been asso ciated with retrolental fibroplasia, phlyc tenular keratoconjunctivitis, lipoid degen eration. penetrating wound, keratokonus, buphthalmos, and trichiasis [1][2][3][4][5][6]. To our knowledge, only a few reported cases have been described of secondary corneal amyloi dosis caused by trichiasis [4.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that Bowman’s layer is sometimes destroyed by amyloid aggregation. 2 , 5 , 6 , 9 Usually, tissue sampling during the early stages is difficult to perform from an ethical point of view, and we were only able to examine the histology of advanced cases of SCA. Moreover, these histological examinations do not always reflect the in vivo structure.…”
Section: Discussionmentioning
confidence: 99%